IMPLEMENTATION OF SCHOOL-BASED MANAGEMENT TO IMPROVE THE QUALITY OF EDUCATION IN ELEMENTARY SCHOOLS - Soraya, Arafatul; Sri Sumarni; Marwah; Uswatun Hasanah (Darul Ilmi Bina Insan Foundation, 2024)
School-Based Management (SBM) is a management approach that enables schools to manage themselves independently. This independence is essentially the responsibility of the school, particularly the principal, to ensure the school can advance under their guidance. In practice, school management requires a comprehensive understanding of basic concepts. The purpose of this article is to discuss the implementation of school-based management in improving the quality of education in primary schools. This writing uses research or literature studies. This review refers to the content of studies or articles (written works). Through a literature review, the research results provide an explanation of the concept of school-based management, the implementation of school-based management, strategic targets for improving education quality through school-based management, obstacles to the implementation of School-Based Management, and more. Examples applied in educational units show that schools implementing this model are able to transform primary education, thereby strengthening their human resources